Identification of Risk Management Implementation on Environmental Issues Related to Airport Operations : Case Study of Rahadi Oesman Airport - Amran Hamid, Rusyda; Djakman, Chaerul D. (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
This study aimed to evaluate environmental risks based on risk assessment analysis and implement effective risk management to support Rahadi Oesman Airport operations. The research design and methodology used an evaluative case study approach with qualitative methods. Data were collected through a literature review, interviews with two airport employees, including the airport chief, and direct observation in the field. Analysis was conducted by identifying issues, categorizing data, and evaluating findings to develop recommendations and risk reduction strategies. The main findings of this study show that environmental risks such as bad weather, non-standard aircraft spacing, foreign objects, security issues, and wildlife around the airport can cause flight delays, cancellations, or accidents. Risk management includes reducing the use of vehicles with engines, saving water and lights, and using human labour for ground handling activities. The implications of this study emphasise the importance of environmental risk control strategies, strict implementation of SOPs, and training for airport staff. This research contributes to environmental risk management practices in the aviation industry and provides valuable insights for other airports facing similar challenges. Nonetheless, this study has limitations on the number of respondents and the use of questionnaires that need to be further developed.